See Change: VLT spectroscopy of a sample of high-redshift Type Ia supernova host galaxies. Issue 4 (15th May 2020) - Williams, S C; Hook, I M; Hayden, B; Nordin, J; Aldering, G; Boone, K; Goobar, A; Lidman, C E; Perlmutter, S; Rubin, D; Ruiz-Lapuente, P; Saunders, C; et al.
ABSTRACT: The Supernova Cosmology Project has conducted the 'See Change' programme, aimed at discovering and observing high-redshift (1.13 ≤ z ≤ 1.75) Type Ia supernovae (SNe Ia). We used multifilter Hubble Space Telescope ( HST ) observations of massive galaxy clusters with sufficient cadence to make the observed SN Ia light curves suitable for a cosmological probe of dark energy at z > 0.5. This See Change sample of SNe Ia with multi-colour light curves will be the largest to date at these redshifts. As part of the See Change programme, we obtained ground-based spectroscopy of each discovered transient and/or its host galaxy. Here, we present Very Large Telescope (VLT) spectra of See Change transient host galaxies, deriving their redshifts, and host parameters such as stellar mass and star formation rate. Of the 39 See Change transients/hosts that were observed with the VLT, we successfully determined the redshift for 26, including 15 SNe Ia at z > 0.97. We show that even in passive environments, it is possible to recover secure redshifts for the majority of SN hosts out to z = 1.5. We find that with typical exposure times of 3−4 h on an 8-m-class telescope we can recover ∼75 per cent of SN Ia redshifts in the range of 0.97 < z < 1.5. Furthermore, we show that the combination of HST photometry and VLT spectroscopy is able to provide estimates of host galaxy stellar mass that are sufficiently accurate for use in a mass-step correction in the cosmological analysis.